Lesotho : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report, 2004)
This paper presents Ex Post Assessment of Longer-Term Program Engagement for Lesotho. The paper reviews the experience of the IMF's engagement in Lesotho during the period 1991-2004, and briefly presents economic developments prior to these arrangements. It reviews performance under IMF-supported programs and analyzes the main factors accounting for that performance. The paper draws lessons from these program experiences and considers the main challenges facing Lesotho. The role that the IMF can play in helping the authorities to meet those challenges is also examined.